Adolescent-Peer Relationships, Separation and Detachment From Parents, and Internalizing and Externalizing Behaviors: Linkages and Interactions. (May 2015) - Jager, Justin; Yuen, Cynthia X.; Putnick, Diane L.; Hendricks, Charlene; Bornstein, Marc H.
Most research exploring the interplay between context and adolescent separation and detachment has focused on the family; in contrast, this investigation directs its attention outside of the family to peers. Utilizing a latent variable approach for modeling interactions and incorporating reports of behavioral adjustment from 14-year-old adolescents ( N = 190) and their mothers, we examine how separation and detachment relate to adolescent-peer relationships, and whether peer relationships moderate how separation and detachment relate to adolescent internalizing and externalizing behaviors. Positive peer relationships were both associated with lower detachment and sharply attenuated relations between detachment and higher adolescent internalizing and externalizing. Separation from parents was unrelated to peer relationships, and regardless of whether peer relationships were positive, separation was not related to adolescent internalizing and externalizing. We integrate these findings with those from family-focused investigations and discuss their substantive and clinical implications.